2016
DOI: 10.1139/cjc-2016-0230
|View full text |Cite
|
Sign up to set email alerts
|

Chemical repair of protein carbon-centred radicals: long-distance dynamic factors

Abstract: The thermodynamic and kinetic study of the repair reactions of three damaged aliphatic amino acids (alanine, valine, and leucine) with dihydrolipoic acid (DHLA) in a polar and a nonpolar solvent is presented in this work. Two simplified protein models were explored in the most common conformations (alpha helix and beta sheet). Calculations are performed at the M06-2X-SMD/6-31++G(d,p) level of theory. DHLA has shown to be an excellent antioxidant repair agent through hydrogen-transfer reaction involving the thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 53 publications
0
12
0
Order By: Relevance
“…This model requires the calculation of the steady-state Smoluchowski rate constant for an irreversible diffusion-controlled bimolecular reaction [ 32 ], and the application of the Stokes–Einstein approach [ 33 , 34 ]. Details on this methodology and the equations used can be found in previous publications [ 35 , 36 , 37 , 38 , 39 ]. This methodology has been successfully used in studies of primary and secondary antioxidant activity [ 22 , 23 , 24 , 35 , 36 , 37 , 38 , 39 , 40 ].…”
Section: Computational Detailsmentioning
confidence: 99%
“…This model requires the calculation of the steady-state Smoluchowski rate constant for an irreversible diffusion-controlled bimolecular reaction [ 32 ], and the application of the Stokes–Einstein approach [ 33 , 34 ]. Details on this methodology and the equations used can be found in previous publications [ 35 , 36 , 37 , 38 , 39 ]. This methodology has been successfully used in studies of primary and secondary antioxidant activity [ 22 , 23 , 24 , 35 , 36 , 37 , 38 , 39 , 40 ].…”
Section: Computational Detailsmentioning
confidence: 99%
“…The SMD model, which is based on the quantum mechanical charge density of the solute interacting with a continuum description of the solvent, is considered a universal solvation model, due to its applicability to any charged or uncharged solute in any solvent or liquid medium for which a few key descriptors are known [36]. The M06 and M06-2X functionals (or their previous versions, the M05 and M05-2X functionals) combined with the SMD continuum solvation model have been successfully used in various kinetic studies in solution [10][11][12][13][14][15][25][26][27][28].…”
Section: Computational Detailsmentioning
confidence: 99%
“…More detailed information on these expressions and their application in various studies can be found elsewhere [10][11][12][13][14][15]45].…”
Section: Computational Detailsmentioning
confidence: 99%
See 2 more Smart Citations